Collaborative Work in Virtual Learning Environments: Some Reflections and Prospects of Students - Mora-Vicarioli, Francisco (2016)
The collaborative work in virtual learning environments becomes more relevant at a time when technology is used intensively. This paper shows the results of research conducted at the Universidad Estatal a Distancia (UNED) in Costa Rica, about students’ perceptions around the concept and implications of collaborative work in two online courses provided by Dirección de Extensión Universitaria (Dirextu). The aim of this study is to establish the difference between collaborative work and group work as well as knowing the tools that can be used to promote this type of activity in virtual learning environments. The methodology used for this article applied a survey to two groups of students, each belonging to two different virtual courses of the Dirección de Extensión Universitaria (Dirextu). This study was based on quantitative research and applied an instrument with open and closed questions. The analysis process of the results was performed with the help of tables and figures (graphs). Finally, the study exposes a series of conclusions and recommendations among which we highlight the following: students do like collaborative activities because they diversify the teaching modes and improve the learning styles.